1971
DOI: 10.1007/bf02531131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatty acid concentration and positional specificity on maize triglyceride structure

Abstract: The effects of fatty acid concentration and positional specificity on maize triglyceride structure were evaluated from the stereospecific analyses of triglycerides from 12 genotypes. The fatty acids at each position were influenced by the fatty acid concentration in the total triglyceride except for the saturates in the 2 position. The fatty acid concentration had the greatest effect on the fatty acid composition of position 3. The existence of positional specificity was evident from the nonrandom distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 3 publications
6
25
0
Order By: Relevance
“…These oils may exhibit a preferentially or genetically controlled distribution of fatty acids (16,17). However for sunflower oil, the variation was less than an E of 4 for TGMS Downloaded by [McGill University Library] greater than 10%.…”
Section: Methodsmentioning
confidence: 94%
“…These oils may exhibit a preferentially or genetically controlled distribution of fatty acids (16,17). However for sunflower oil, the variation was less than an E of 4 for TGMS Downloaded by [McGill University Library] greater than 10%.…”
Section: Methodsmentioning
confidence: 94%
“…Stereospecific plots of plant lines that differ in acyl group composition show linear relationships between the percentages of an acyl group on the sn-1, -2, and -3 positions and the percentage of that acyl group in the total TAG. This relation has been shown for several species (2)(3)(4)(5)(6). Fatemi and Hammond (4) suggested that these plots would be helpful in identifying TAG distribution mutants since such mutants would yield data points that departed from the linear plots typical of the species.…”
mentioning
confidence: 93%
“…More advanced research carried out in the chemistry of triacylglycerols of vegetable oils by 13 C NMR spectroscopy showed that unsaturated and carbonyl carbon resonances of acyl chains enabled the regiospecific analysis of triacylglycerols by determining the acyl chain composition of 1,3 and 2-glycerol positions, no differentiation of sn-1 and sn-3 positions being allowed. The attachment specificity of unsaturated chains at 2-position was also calculated, thus improving substantially the knowledge of molecular structure of triacylglycerols [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The attachment specificity of unsaturated chains at 2-position was also calculated, thus improving substantially the knowledge of molecular structure of triacylglycerols [5][6][7][8]. The regiospecific analysis of vegetable oils from different botanical origins was successfully performed by a new quantitative 13 C NMR methodology based on the resonances of carbonyl carbons of triacylglycerols [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation